Philippine criminal law dictionary - Salinas, Karis Dawn M.; Faderon, Rosalie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
Not everyone possesses legal knowledge. Unfortunately, the poor and the uneducated are the ones more involved in crimes. Since English is the chosen language of the practice of law in the Philippines, this creates alienation among those accused of crimes from the legal knowledge. The main problem is that it is too difficult to quickly find the required legal information.
This research is intended to produce a criminal law dictionary that would help more indigent Filipinos to understand the law better. Also, it aims to advocate similar projects that would push the practice of law in the Philippines to use Filipino in court and in legal documents. It also seeks to point out the difficulties in making bilingual dictionaries in the field of law.
To do this, the researcher collected terms from the Revised Penal Code and translated them using the top-down approach. This method used previously constructed translation tools such as Peralejo's Ang Binagong Kodigo Penal and Moreno's Philippine Law Dictionary. Term analysis involved lexicographical work. Additional grammatical information was added such as the part of speech covered by the term. After which, the terms were classified according to the sub-topics of Criminal Law they pertain to. Experts' advice was sought regarding the validity and applicability of ambiguous terms. Experts are comprised of legal practitioners who are first language Filipino speakers.
The researcher was able to translate 940 terms from the Revised Penal Code. These terms are arranged alphabetically and are described with the parts of speech, single or multiple definitions, and are categorized according to the titles they fall under.
Thesis (Bachelor of Library and Information Science)
Keywords: Criminal law -- Philippines -- Dictionaries